APPLICABILITY OF THE CLOUDY LOGIC IN THE DESLIGNIFICATION PROCESS OF ELEPHANT GRASS IN THE PRE-TREATMENT WITH NAOH - Zullo Godinho, Emmanuel; de Lima Caneppele, Fernando; Vagner Gasparotto, Helio (Revista Brasileira de Engenharia de Biossistemas, 2021)
Elephant grass has great potential for the production of bioethanol, with emphasis on field production and industrial handling. The pre-treatment process in biomass is essential to obtain high yields in bioethanol production. Therefore, optimization is essential for cost reductions and increased financial profitability. As a result, it aimed to develop a system based on fuzzy rules, which optimized the pre-treatment process with NaOH in elephant grass. The fuzzy model was developed using two input and one output variables, namely concentration, temperature and lignin, respectively. Analysis of the effects of concentration and temperature was performed using three-dimensional surfaces and contour maps of the output variable. It was found that the variables related to lignin are largely affected by a low dose of NaOH concentration and with a medium to low temperature. In general, it is concluded that the region between 0.4 to 0.6% of NaOH concentration, combined with a temperature between 80.5 to 85.0°C, the best results are verified for the studied biometric variable, lignin.